Highly Luminous N 3- -Substituted Li 2 MSiO 4-δ N 2/3δ :Eu 2+ (M = Ca, Sr, and Ba) for White NUV Light-Emitting Diodes - Kim, Donghyeon; Ji, Choon Woo; Lee, Jungjun; Bae, Jong Seong; Hong, Tae Eun; Ahn, Sung Il; Chung, In; Kim, Seung Joo; Park, Jung Chul (ACS Omega, 2019)
The N 3- -substituted Li 2 MSiO 4 :Eu 2+ (M = Ca, Sr, and Ba) phosphors were systematically prepared and analyzed. Secondary-ion mass spectroscopy measurements revealed that the average N 3- contents are 0.003 for Ca, 0.009 for Sr, and 0.032 for Ba. Furthermore, the N 3- incorporation in the host lattices was corroborated by infrared and X-ray photoelectron spectroscopies. From the photoluminescence spectra of Li 2 MSiO 4 :Eu 2+ (M = Ca, Sr, and Ba) phosphors before and after N 3- doping, it was verified that the enhanced emission intensity of the phosphors is most likely due to the N 3- doping. In Li 2 MSiO 4 :Eu 2+ (M = Ca, Sr, and Ba) phosphors, the maximum wavelengths of the emission band were red-shifted in the order Ca < Ba < Sr, which is not consistent with the trend of crystal field splitting: Ba < Sr < Ca. This discrepancy was clearly explained by electron-electron repulsions among polyhedra, LiO 4 -MO n , SiO 4 -MO n , and MO n -M'O n associated with structural difference in the host lattices. Therefore, the energy levels associated with the 4f 6 5d energy levels of Eu 2+ are definitely established in the following order: Li 2 CaSiO 4 :Eu 2+ > Li 2 BaSiO 4 :Eu 2+ > Li 2 SrSiO 4 :Eu 2+ . Furthermore, using the Williamson-Hall (W-H) method, the determined structural strains of Li 2 MSiO 4 :Eu 2+ (M = Ca, Sr, and Ba) phosphors revealed that the increased compressive strain after N 3- doping induces the enhanced emission intensity of these phosphors. White light-emitting diodes made by three N 3- -doped phosphors and a 365 nm emitting InGaN chip showed the (0.333, 0.373) color coordinate and high color-rendering index (R a = 83). These phosphor materials may provide a platform for development of new efficient phosphors in solid-state lighting field.